Pengembangan Media E-Flipbook Materi Keragaman Sosial Budaya terhadap Sikap Toleransi Peserta Didik Kelas IV - Inayah, Nurul; Aeni, Ani Nur; Hanifah, Nurdinah (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to formulate learning media in the form of e-flipbooks of socio-cultural diversity material on tolerance attitudes in grade 4th students in elementary school. Research method applied in this study is research and development (RnD), utilizing ADDIE development model which includes stages of analysis, design, development, implementation, evaluation. The feasibility level of e-flipbook learning media is based on validation results of material and media experts, while the results of its use are measured through a self-assessment sheet on tolerance attitudes to students. The feasibility results assessed by material experts acquired an average score 84% with category “very feasible” while the feasibility results assessed by media experts acquired an average score 90% with category “very feasible”. The conclusion of this study, based on the results of the self-assessment sheet on the tolerance attitude of students carried out after using the e-flipbook learning media, showed an average score of 84% which is categorized as very good. Recommendations for further researchers to develop research that improves tolerance attitudes or other affective attitudes to improve future research.